Depression and Suicidal Ideation among Adolescents in Kuching, Malaysia - Ang, Ai Ling (Malaysian Psychiatric Association, 2017)
Background: There is limited research on adolescent mental health despite the increasing trend of adolescent depression and suicide worldwide. The study aimed to estimate the prevalence of depression and suicidal ideation among adolescents in Kuching, Malaysia. The factors associated with depression as well as the relationship between depression and suicidal ideation was investigated. Methods: A cross-sectional study was conducted among students in public secondary schools in urban and rural areas. The students randomly selected via multi-stage sampling completed the Malay language version of Child Depression Inventory (CDI) and Beck Scale for Suicidal Ideation (BSS). Results: The prevalence of depression in the study was 26.2%. Binary logistic regression analysis shown that the variables significantly associated with depression were race (p=0.028), type of class (p<0.001), mother's education level (p=0.036), type of housing (p=0.036), parents' marital status (p=0.012), alcohol intake (p=0.005), stealing (p<0.001) and history of disciplinary record (p=0.005). The factors identified as predictors of depression based on multivariable logistic regression were being in Arts stream class (p=0.004, Adj. OR 2.4, [95% CI: 1.34-4.41]), having parents who had separated, divorced or widowed (p=0.017, Adj. OR 3.1, [95% CI: 1.23-7.95]) and history of stealing (p<0.001, Adj. OR 3.3, [95% CI: 1.85-5.78]). The prevalence of suicidal ideation in the study sample was 20.0%. The total CDI score significantly predicted total BSS score based on multiple linear regression analysis (p<0.001). Discussion: Students in Arts stream with parents who had separated, divorced or widowed and had history of stealing were predicted to be at risk for depression. The multiple linear regression analysis result indicated that the presence of depression was significantly associated with suicidal ideation. The rate of depression and suicidal ideation in the sample is high. There is a need for greater collaboration and concerted effort among various agencies to enhance mental health promotion and suicidal prevention among adolescents.